Orexin effect on physiological pulsations of the human brain - Matti Järvelä; Janne Kananen; Heta Helakari; Vesa Korhonen; Niko Huotari; Tommi Väyrynen; Katariina Hautamäki; Lauri Raitamaa; Johanna Tuunanen; Mika Kallio; Johanna Piispala; Hanna Ansakorpi; et al. (Proceedings of the National Academy of Sciences, 2025)
Sleep promotes cerebrospinal fluid (CSF) to interstitial fluid (ISF) exchange in the brain facilitated by brain pulsations. Especially brain vasomotion and arterial pulsations modulated by noradrenaline drive the intracranial fluid dynamics. Narcolepsy type 1 (NT1) entails lessened orexinergic output to wake-promoting systems including the noradrenergic locus coeruleus. As arousal state and noradrenergic signaling affect CSF-ISF clearance, we chose patients with NT1 as a human orexin-targeted model of sleep-related pathology bridging the gap between healthy awake and sleep with respect to CSF flow pulsations. We also investigated the sensitivity of magnetic resonance encephalography to detect flow with a phantom model and sought to replicate earlier pulsation findings in sleep. In this case–control study, we used fast functional MRI to map brain pulsations in groups of healthy sleeping controls (n = 13), healthy awake controls (n = 79), and awake NT1 (n = 21) patients. We measured the very low frequency (0.008 to 0.1) and cardiorespiratory frequencies and calculated in each frequency band the coefficient of variation, spectral power, and full band spectral entropy to obtain brain pulsation maps. We uncovered a brain pulsation profile from healthy waking to sleep to a sleep-related pathology NT1 prominently affected in the vascular-related vasomotor and brain arterial pulsations. Our results established how drivers of brain hydrodynamics are affected by a specific loss of key neurotransmitter governing arousal compared to healthy sleep. We also showed with a phantom model that MREG is sensitive to flow-related signal changes and solidified evidence of brain pulsations in the healthy states of sleep and wakefulness.